The Role of Advertising and Brand Ambassadors for Casuale Project Brand Sales - Sukandi, Pipin; Pratama, Fauzan Yafa Zain (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2023)
The role of advertising and brand ambassadors has a big effect on one of the local brands, Casuale Project, especially to increase sales. The Casuale Project team made an update to be able to increase sales of its products. However, what happens here is that when advertising has been updated and brand ambassadors have been appointed for Casuale Project, potential consumers here still feel less about Casuale Project products. This study aims to analyze how the role of advertising and brand ambassadors for sales on the Casuale Project brand. This research uses qualitative research and is processed using data obtained from interviews. The results of this study show that the role of advertising does not really play a big role in increasing sales, it turns out that sales can increase because it uses a brand ambassador strategy to sell its products.